Do selective schooling systems increase inequality?. (25th February 2019) - Burgess, Simon; Dickson, Matt; Macmillan, Lindsey
Abstract: We investigate the impact on earnings inequality of a selective education system in which school assignment is based on initial test scores. We use a large, representative household panel survey to compare adult earnings inequality of those growing up under a selective education system with those educated under a comprehensive system in England. Controlling for a range of background characteristics and the current location, the wage distribution for individuals who grew up in selective schooling areas is substantially and significantly more unequal. The total effect sizes are large: 24% of the raw 90–10 earnings gap and 19% of the conditional 90–10 earnings gap can be explained by differences across schooling systems.